Peningkatan Minat Dalam Penggunaan Kartu Kredit Syariah dengan Pendekatan Kepercayaan, Sikap dan Pendapatan di Kabupaten Labuhanbatu Utara - Audina Rizka Zahra; Marwan Batubara; Purnama Ramadani Silalahi; Rendi Prayoga; Dea Putri Amanda (VISA: Journal of Vision and Ideas, 2021)
In non-cash transactions, Islamic credit cards have become a way of life in modern economic culture. The use of Islamic credit cards has risen and fallen throughout time due to a variety of variables. Trust, attitudes, and income are some of these determinants. The goal of this research was to see how beliefs, attitudes, and income affected interest in using Islamic credit cards. The basic data for this study comes from interviews with 38 participants in North Labuhanbatu Regency who were chosen using a borring sample approach. Multiple linear regression was used to evaluate the data. Each trust, attitude, and income level had a favorable and substantial impact on interest in using a sharia credit card, according to the findings. This study benefits (a) academics by providing proof of concept, and (b) Islamic banks by providing data to assess the factors that impact interest in using a sharia credit card. Keywords: Trust, Attitudes, Income, Islamic Credit Cards